Late Life Depression Detection: An Evidence-Based Guideline - Smith, Marianne (J Gerontol Nurs, 2015)
The disability associated with late life depression makes it an important target for screening. Identifying clinically significant depression symptoms in older adults who have known risk factors provides an important opportunity for early evaluation and treatment. Screening that leads to evaluation and treatment is critical to both preventing depression, and reducing the associated disability, symptom burden, and costs of major depressive disorders (MDD). The guideline described here recommends the 9-item Patient Health Questionnaire (PHQ-9) for screening because it is based on diagnostic criteria for MDD and has the advantages of being brief, self-administered, easily scored and interpreted, and reliable and valid in diverse populations and care settings. Nurses and allied health professionals who provide care to older adults across the continuum of care are uniquely positioned to identify at risk older adults, use depression screening scales, make needed referrals for evaluation and treatment, and monitor outcomes across time.